Blockchain based Transformation in government: review of case studies - Basheska, Julija; Trajkovik, Vladimir (My University, 2018)
Blockchains are immutable digital ledger systems implemented in a distributed way and usually without a central authority. Each transaction in the public ledger is verified by consensus of a majority of the participants in the system. Once entered, information can never be erased. The blockchain contains a certain and verifiable record of every single transaction ever made. It operates in a decentralized peer-to-peer network using cryptographic algorithms to verify, validate and distribute transactions across millions of nodes, enabling the secure, auditable, transmission of assets without intervention by a central authority. The economic, political, humanitarian, and legal system started realizing the benefits of Bitcoin and blockchain technology and the fact that this is potentially an extremely powerful technol ogy that could have the capacity to modify many aspects of society and its operations. This document provides a short, high-level technical overview of the blockchain technology. It provides a review of application beyond crypto-currencies and financial applications through use cases in government and public services.
Keywords: Blockchain, distributed systems, eGovernment, digital transformation